NKG2D Enhances Double-Negative T Cell Regulation of B Cells - Hu, Shi-hua; Zhang, Long-hui; Gao, Jie; Guo, Jing-heng; Xun, Xiao-dong; Xiang, Xiao; Cheng, Qian; Li, Zhao; Zhu, Ji-ye (Frontiers in Immunology, 2021)
Numerous studies reported a small subpopulation of TCRαβ+CD4-CD8- (double-negative) T cells that exert regulatory functions in the peripheral lymphocyte population. However, the origin of these double-negative T (DNT) cells is controversial. Some researchers reported that DNT cells originated from the thymus, and others argued that these cells are derived from peripheral immune induction. We report a possible mechanism for the induction of nonregulatory CD4+ T cells to become regulatory double-negative T (iDNT) cells in vitro. We found that immature bone marrow dendritic cells (CD86+MHC-II- DCs), rather than mature DCs (CD86+MHC-II+), induced high levels of iDNT cells. The addition of an anti-MHC-II antibody to the CD86+MHC-II+ DC group significantly increased induction. These iDNT cells promoted B cell apoptosis and inhibited B cell proliferation and plasma cell formation. A subgroup of iDNT cells expressed NKG2D. Compared to NKG2D- iDNT cells, NKG2D+ iDNT cells released more granzyme B to enhance B cell regulation. This enhancement may function via NKG2D ligands expressed on B cells following lipopolysaccharide stimulation. These results demonstrate that MHC-II impedes induction, and iDNT cells may be MHC independent. NKG2D expression on iDNT cells enhanced the regulatory function of these cells. Our findings elucidate one possible mechanism of the induction of peripheral immune tolerance and provide a potential treatment for chronic allograft rejection in the future.